2011
DOI: 10.1021/np200350b
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Polyketides from the Jellyfish-Derived Fungus Paecilomyces variotii

Abstract: Four new polyketides (1-4) were isolated from the fungus Paecilomyces variotii, which was derived from the jellyfish Nemopilema nomurai. The planar structures and relative configurations of these polyketides were elucidated on the basis of spectroscopic analyses, including 2D NMR experiments. The compounds showed inhibitory activity against pathogenic bacteria including methicillin-resistant Staphylococcus aureus 3089 and multi-drug-resistant Vibrio parahemolyticus 7001 with MIC values in the range 5-40 μg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 19 publications
0
48
0
1
Order By: Relevance
“…The antimicrobial activity of the methanol crude extract from marine-derived Paecilomyces sp. was determined for MRSA, Escherichia coli, A. hydrophila and C. albicans at 18, 6, 9 and 7 mm, respectively (Liu et al, 2011). Ethyl acetate extract of P. variotii FEL24 presented antimicrobial activities ranged from 19 to 35 mm (Silva et al, 2011).…”
Section: Determination Of the Appropriate Solvent(s) For Extraction Omentioning
confidence: 99%
See 2 more Smart Citations
“…The antimicrobial activity of the methanol crude extract from marine-derived Paecilomyces sp. was determined for MRSA, Escherichia coli, A. hydrophila and C. albicans at 18, 6, 9 and 7 mm, respectively (Liu et al, 2011). Ethyl acetate extract of P. variotii FEL24 presented antimicrobial activities ranged from 19 to 35 mm (Silva et al, 2011).…”
Section: Determination Of the Appropriate Solvent(s) For Extraction Omentioning
confidence: 99%
“…These compounds showed inhibitory activity against pathogenic bacteria, including methicillin-resistant Staphylococcus aureus 3089 and multi-drug-resistant Vibrio parahemolyticus 7001 (Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new compound showed cytotoxicity against human and marine pathogens, including multidrug-resistant strains. Liu et al reported that this natural analogue also exhibits mild antibacterial activity against Escherichia coli DC2, Streptococcus iniae FP5228, and methicillin-resistant S. aureus (MRSA) [47].…”
Section: An Anacardic Acid Analoguementioning
confidence: 99%
“…Ecological interactions have been evolved not only between the host and their endozoic microorganisms, but also between the encozoic bacteria and fungi, which share a common substrate in either a symbiotic or competitive manner [1,2]. Unlike free-living microorganisms, encozoic microorganisms produce unique secondary metabolites in a special ecological niche, which deliver interesting pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%